2020
DOI: 10.3390/su12072789
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence, Transport and the Smart City: Definitions and Dimensions of a New Mobility Era

Abstract: Artificial intelligence (AI) is a powerful concept still in its infancy that has the potential, if utilised responsibly, to provide a vehicle for positive change that could promote sustainable transitions to a more resource-efficient livability paradigm. AI with its deep learning functions and capabilities can be employed as a tool which empowers machines to solve problems that could reform urban landscapes as we have known them for decades now and help with establishing a new era; the era of the “smart city”.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(122 citation statements)
references
References 129 publications
(139 reference statements)
0
121
0
1
Order By: Relevance
“…The AI paradigm and its technology-enabled solutions-whether it is autonomous driving, home automation (so-called domotics), robotics, chatbots, or advanced data analytic tools-have opened up new opportunities for cities, where most of the world population resides, where most of the production and consumption activities take place, and also where most of the negative environmental externalities are generated [15,16]. While some scholars see AI as an opportunity to advance smart cities (or smartness of cities) [17][18][19][20][21], others see AI generating a whole new city brand, especially when the AI applications become mainstream in our cities [22]. In other words, in the near future, we will see a trend to build 'artificially intelligent cities' from scratch, or to retrofit traditional cities, converting them into artificially intelligent ones.…”
Section: Introductionmentioning
confidence: 99%
“…The AI paradigm and its technology-enabled solutions-whether it is autonomous driving, home automation (so-called domotics), robotics, chatbots, or advanced data analytic tools-have opened up new opportunities for cities, where most of the world population resides, where most of the production and consumption activities take place, and also where most of the negative environmental externalities are generated [15,16]. While some scholars see AI as an opportunity to advance smart cities (or smartness of cities) [17][18][19][20][21], others see AI generating a whole new city brand, especially when the AI applications become mainstream in our cities [22]. In other words, in the near future, we will see a trend to build 'artificially intelligent cities' from scratch, or to retrofit traditional cities, converting them into artificially intelligent ones.…”
Section: Introductionmentioning
confidence: 99%
“…One of the building blocks for any smart city is its reliance on Intelligent transport systems (ITSs). Emerging mobility paradigms that are based on connected and autonomous vehicles (CAV), UAV, Mobility as a service (Maas) can serve as enabling technologies that paved the way for enhanced transportation experiences ( Nikitas et al, 2020 ). Autonomous and connected vehicles are one aspect; however, other facets of transportation also need to move towards automation such as highway maintenance, traffic police agents etc ( Menouar et al, 2017 ).…”
Section: Wide-scale Deployment Of Uavs: Barriers Solutions and Implimentioning
confidence: 99%
“…This goal can be achieved primarily through the use of CAVs. With CAVs operating in an SRE context, positive impacts occur in energy saving and space allocation; this is why they could participate in TOD (Transit Oriented Development) programs [19]. A critical aspect has been treated before when describing V2R communications, and it showed that devices have to collect a high amount of data.…”
Section: Smart Roads and Autonomous Vehiclesmentioning
confidence: 99%